Exquisite sensitivity of Polycystin-1 to H2O2 concentration in the endoplasmic reticulum - Elisa Speranza; Ilaria Sorrentino; Alessandra Boletta; Roberto Sitia (Redox Biology)
Aquaporin11 (AQP11) is an endoplasmic reticulum (ER) resident peroxiporin. It allows H2O2 transport from the lumen to the cytosol, guaranteeing redox homeostasis and signaling in and between the two organelles. Interestingly, Aqp11−/− mice develop a fatal, early onset polycystic kidney disease (PKD) similar to Autosomal Dominant PKD, a condition frequently associated with mutations of polycystin-1 (PC-1) in human patients. Here we investigated the molecular mechanisms of AQP11-associated PKD. Using different cell models, we show that transient downregulation of AQP11 selectively prevents the biogenesis of overexpressed PC-1. Expression of catalase in the ER lumen rescues the phenotype, demonstrating a direct role of (H2O2)ER in controlling the complex maturation of PC-1. Analysis of endogenous Pc-1 revealed an additional regulatory role at the pre-translational level. Taken together, our results show that AQP11 controls the complex biogenesis of PC-1 at multiple levels governing H2O2 intra and inter-organellar fluxes, with important implications in the pathogenesis and onset of PKD.